Measurement of Zakat Village Index, Banjarnegara Regency province of Central Java - Azzaki, Muhammad Adnan; Arohman, Arohman; Ramadhan, Fadhil Fuad; Ihsan, Akmal (AL-QARDH, 2022)
The National Amil Zakat Agency (BAZNAS) as a zakat management institution plays a role in tackling poverty through the distribution of zakat funds. Zakat distribution carried out by amil zakat institutions is distributed in the form of consumptive zakat and productive zakat. The form of productive zakat fund assistance that is being distributed by BAZNAS is through Zakat Community Development (ZCD). This program requires measurable instruments to encourage the effectiveness and relevance of the program to the context of its objectives. The purpose of this study was to determine the value of the zakat village index of Mandiraja Wetan Village, Mandiraja District, Banjarnegara Regency, Central Java Province. The analysis tool used is the Zakat Village Index (IDZ) with a calculation method called the Multi-Stage Weigh Index. The result of this study is the value of the zakat village index of Mandiraja Wetan Village of 0.48.